2005
DOI: 10.1021/jo050237j
|View full text |Cite
|
Sign up to set email alerts
|

The First Solid-Phase Synthesis of Bis(oxazolinyl)pyridine Ligands

Abstract: Chiral Pybox (pyridine-2,6-bis(oxazoline)) ligands can be cleanly and efficiently prepared on polystyrene support via a five-step solid-phase synthetic sequence. Cu(I)-complexed polymer-bound Pybox was used as a catalyst in the first heterogeneously catalyzed asymmetric addition of alkynes to imines. Best enantioselectivity was observed with (t)Bu-substituted oxazolines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 20 publications
(19 reference statements)
0
19
0
1
Order By: Relevance
“…Ph Ph-PyBOX * Alternatively, O ' Leary and co -workers immobilized a Cu(I) -and Cu(II) -Ph -PyBOX trifl ate complex on silica due to electrostatic interactions, but the catalyst ' s reusability was studied only during three cycles [68] . The immobilization of the Py -BOX ligand in a Wang resin did not provide a very recyclable system for the same transformation [69] . The reactions performed in IL provided the higher levels of enantiomeric induction, but the water/stearic acid system was more effi ciently recyclable.…”
Section: Py -Box Ligandsmentioning
confidence: 99%
“…Ph Ph-PyBOX * Alternatively, O ' Leary and co -workers immobilized a Cu(I) -and Cu(II) -Ph -PyBOX trifl ate complex on silica due to electrostatic interactions, but the catalyst ' s reusability was studied only during three cycles [68] . The immobilization of the Py -BOX ligand in a Wang resin did not provide a very recyclable system for the same transformation [69] . The reactions performed in IL provided the higher levels of enantiomeric induction, but the water/stearic acid system was more effi ciently recyclable.…”
Section: Py -Box Ligandsmentioning
confidence: 99%
“…Bisia and Singh further optimized the enantioselectivity of these addition reactions by surveying other pybox ligands, cii and Weissberg et al demonstrated the viability of this process with a solid supported pybox catalyst. ciii …”
Section: Enantioselectieve Addition Of Alkyne Nucleophiles To Iminesmentioning
confidence: 99%
“…A series of polymer-bound pybox ligands were prepared by Portnoy [48]. The synthesis of these supported ligands required five steps starting from Wang trichloroacetimidate 107 (Scheme 44).…”
Section: Copper-catalyzed Enantioselective Additionsmentioning
confidence: 99%